Awareness and Usage of Information Retrieval Functionalities Found in the Online Public Access Catalogue by Undergraduates at the University of Venda - Shokane, Mashia; Bopape, Solomon Tsekere (Mousaion: South African Journal of Information Studies, 2023)
Calls for a shift from the Online Public Access Catalogue (OPAC) to discovery systems craft a need for recognising the information-searching behaviour of the current genre of library users. This study examined the undergraduate students’ awareness and usage of information search functionalities that are embedded in OPAC at the University of Venda (UNIVEN) in Limpopo Province, South Africa (SA). Quantitative data were collected using a Google Form questionnaire, the link of which was e-mailed to the participants to complete. A systematic random sampling method was applied to arrive at 563 respondents. The findings revealed that most respondents rated their level of awareness of OPAC as average. Although some were familiar with OPAC search functionalities, such as author-and-title search entries, and preferred using simple search options on OPAC, there were respondents who were not familiar with Boolean operators, truncation and wildcard symbols, proximity operators, and field search. The major variables affecting their information retrieval on OPAC were poor internet connection and their lack of skills in searching for information from OPAC. This study recommends that librarians promote the importance of using all OPAC functionalities and train undergraduates to improve their awareness and optimal usage of OPAC.